2005
DOI: 10.1007/s00125-005-1736-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the physicochemical properties of LDL in type 2 diabetes

Abstract: Atherosclerosis is the leading cause of death in type 2 diabetes. LDL cholesterol and atherosclerosis are related, both in healthy people and those with diabetes; however, people with diabetes are more prone to atheroma, even though their LDL cholesterol levels are similar to those in their non-diabetic peers. This is because LDL particles are modified in the presence of diabetes to become more atherogenic. These modifications include glycation in response to high plasma glucose levels; oxidative reactions med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…The prolonged hypertriglyceridemia following three consecutive meals in males with the MetS and patients with T2DM results in the formation of triglyceride-enriched HDL and LDL particles Insulin resistant states, including the MetS and T2DM, are associated with decreased plasma HDL cholesterol concentration, whereas LDL cholesterol concentration is usually normal. However, in T2DM the metabolism of LDL is modified, rendering the lipoprotein particles more atherogenic (Scheffer et al, 2005). Furthermore, it has been shown that high-fat intake is associated with oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The prolonged hypertriglyceridemia following three consecutive meals in males with the MetS and patients with T2DM results in the formation of triglyceride-enriched HDL and LDL particles Insulin resistant states, including the MetS and T2DM, are associated with decreased plasma HDL cholesterol concentration, whereas LDL cholesterol concentration is usually normal. However, in T2DM the metabolism of LDL is modified, rendering the lipoprotein particles more atherogenic (Scheffer et al, 2005). Furthermore, it has been shown that high-fat intake is associated with oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetes, a condition with accelerated atherosclerosis, LDL cholesterol is frequently normal although compositional differences have been described [42]. The postprandial lipoproteins are known to influence LDL composition [43], but are also atherogenic in their own right [5], and it is probably of considerable importance that there is a specific Apo B48 receptor on the macrophage [44].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported different LDL modifi cations in diabetics due to oxidation and glycosylation, resulting in the presence of more atherogenic LDL particles in these patients ( 47 ). Indeed, the increased cardiovascular risk of DM patients has been related to the presence of small dense LDL particles ( 48 ), which have been shown to be more atherogenic and may explain, at least in part, the higher risk of those patients even having similar LDLcholesterol plasma concentrations than control subjects ( 49 ).…”
Section: Cathepsin D-cleaved Apoa-i Exhibits Increased Ldl Binding Abmentioning
confidence: 99%